O uso da técnica HP-GPC na caracterização de asfaltos brasileiros puros e modificados por SBS - Lucena, Maria da Conceição Cavalcante (2005)
The heterogeneity of the asphalt cement (AC) produced in Brazilian refineries and the discovery of recent Brazilian petroleum make necessary a study of techniques that could detect differences not observed in empirical analysis. In this study the gel permeation chromatograph (GPC) is used to characterize a pure and a modified AC's with a styrene-butadiene-styrene (SBS) copolymer produced in Brazilian refineries, originated from different sources and refining processes. The main objective is to establish correlations between the results obtained from this technique and the rheological properties of the AC's. The chromatograms of the samples presented a great dispersion of molecular weights. Three strips of molecular weights (high, medium and low) were noted. It was observed that AC's from different origins and refining processes showed diverse molecular weights distribution being possible to distinguish the samples from the amount of high molecular weight. The presence of SBS in modified AC's contributed to increase the amount of high molecular weight compounds. Comparing the results from GPC and viscosity it was noted a good correlation being observed an increment of the viscosity with the increase of the content of compounds of high molecular weight.